Evaluating lymphocyte change rate and lactate as predictors of prognosis in critical COVID-19 patients in the intensive care unit - Tang, Yuxiu; Yang, Jin; Chen, Liquan; Liu, Xueke; Chen, Zhen; Lin, Jiaxi; Jin, Jun; Wei, Yao (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundStudies have shown that lymphocyte counts and lactate (LAC) levels have a certain relationship with the prognosis of COVID-19 patients. In the present study, we aimed to determine the predictive effects of new indicator lymphocyte change rate and LAC on the prognosis of COVID-19 patients.MethodsIn the present study, we retrospectively analyzed the clinical data of 137 adult patients (≥ 18 years old) diagnosed with the COVID-19 Omicron variant, who were admitted to the comprehensive, respiratory, or infection ICU of our hospital, between November 2022 and February 2023. Cox regression and causal mediation analyses were used to evaluate the relationship between the clinical test data and patient prognosis.ResultsA total of 137 patients with COVID-19 were included in the present study, 77.40% of whom were male, with an average age of 73 years and an overall mortality rate of 51.8%. Multifactorial logistic regression analysis showed that LAC (odds ratio [OR], 0.05; 95% confidence interval [CI], 0–0.1; P = 0.047] and the weekly rate of change in LYM (change in LMY over the course of a week/LYM on the day of admission) had a good predictive value for the prognosis of patients, while respiratory-related indicators had no significant relationship with prognosis (P > 0.05). The combined predictive value of LAC and the weekly rate of change in LYM was even greater, with an area under the curve of 0.7629. In terms of prognosis, 1.75 mmol/L was set as the cut-off value for LAC (sensitivity, 57.7%; specificity, 75.8%). The mortality rate of patients with LAC > 1.75 mmol/L was significantly higher than that those with LAC < 1.75 mmol/L, and NLR was found to have a mediating effect in lactate-mediated death.ConclusionIn summary, lymphocyte change rate combined with LAC had the greatest predictive value for COVID-19 ICU patient prognosis, while respiratory-related indicators had no significant relationship with prognosis, so we suggest the increase of LAC in COVID-19 patients may be caused by microcirculatory disturbances.